Host response to brood parasitism in two species of diving duck - Dugger, B D; Blums, P; Fredrickson, L H (Wildfowl, 1999)
We used egg addition experiments and naturally parasitised nest of Common Pochard Aythya ferina and Tufted Duck A. fuligula to look for three host responses to brood parasitism; nest abandonment, egg discrimination, and between-year nest site movement. Parasitised females did not abandon nests more often (P = 0.26), discriminate against parasite eggs (P’s >/= 0.38) or move their nests a greater distance (P’s >/= 0.39) than non-parasitised females for either species. Host female Common Pochards and Tufted Ducks do not discriminate against parasitic eggs once they are added to the nest.